UTILIZING CONVEX HULL AND CONCAVE HULL ALGORITHMS FOR OPTIMIZING THE DISTRIBUTION OF BASEPOINTS ALONG THE INDIAN OCEAN COASTLINE - Wahyuni, Eka
One of the challenges faced by Indonesia as an archipelagic nation is the determination and establishment of its maritime boundaries. The maritime boundaries of an archipelagic state are defined based on the configuration of base points. So far, the determination of base point configurations in Indonesia has been done manually. This manual approach introduces subjectivity in selecting and drawing maritime boundary lines. In relation to this issue, an automated approach is proposed for determining base point configurations while still adhering to UNCLOS 1982. This automation is expected to generate more optimal base points based on the criteria of being outermost, objective, and academically and legally grounded in international standards. This Final Project is conducted with the aim of obtaining the appropriate algorithm to optimize the configuration of base points used as a reference in determining Indonesia's maritime boundaries. The study area of this Final Project encompasses the baseline segment formed from TD.148A to TD.158. The methods used for the Convex Hull concept are Jarvis March and Graham Scan, while for the Concave Hull concept, the Alpha Shape method with varying threshold values is employed. In the processing phase, zero-contour lines on the Marine Chart are digitized, and then vertex extraction is performed to obtain the outermost points. These coordinates of the outermost points are used as input for the Convex Hull and Concave Hull processing. Based on the results, the Graham Scan and Jarvis March methods produce identical distributions of base points. The Alpha Shape method yields varying distributions of base points depending on the threshold values used. Additionally, five new base points are identified, which can serve as recommendations for determining more optimal base points. In this Final Project's study area, the most appropriate method to use is the Alpha Shape method with a threshold value of 0.3, as it still complies with UNCLOS 1982 and provides an expansion of inland waters by 14,661 km2.